Epididymal Adenomatoid Tumor: A Very Rare Paratesticular Tumor of Childhood - Ioannis Patoulias; Christos Kaselas; Dimitrios Patoulias; Constantine Theocharides; Maria Kalogirou; Konstantinos Farmakis; Thomas Feidantsis (Case Reports in Medicine)
Adenomatoid tumor is an uncommon benign mesothelial neoplasm, usually localized in the epididymis. It is the most common paratesticular tumor of middle-aged patients (average age of clinical presentation: 36 years). However, these tumors in pediatric and pubertal patients are extremely rare. Due to their rarity, we present a case of adenomatoid tumor of the tail of the epididymis in a 16-year-old patient. After systematic research of the current literature, we did not find another case report of epididymal adenomatoid tumor in a male patient aged 16 years old or less. This notice and our concern, as well, about the patient’s surveillance protocol during the postoperative period were the motive for this case study.